2006
DOI: 10.1017/s0265021506000184
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous baroreflex cardiac sensitivity in end-stage liver disease

Abstract: These results confirm that the baroreflex sensitivity is depressed in end-stage liver disease in line with an autonomic nervous system imbalance. The liver transplantation reverses this disturbance only in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Several studies have reported the presence of an autonomic neuropathy in cirrhosis, and most authors agree that the presence of autonomic dysfunction is related with the severity of liver disease, irrespective of its aetiology (15, 16, 18). A decrease in BRS in cirrhotic patients has been described both in experimental (13, 21, 22) and clinical studies (6, 23–26). In most human studies, the severity of cirrhosis was established according to clinical parameters and Child–Pugh score.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported the presence of an autonomic neuropathy in cirrhosis, and most authors agree that the presence of autonomic dysfunction is related with the severity of liver disease, irrespective of its aetiology (15, 16, 18). A decrease in BRS in cirrhotic patients has been described both in experimental (13, 21, 22) and clinical studies (6, 23–26). In most human studies, the severity of cirrhosis was established according to clinical parameters and Child–Pugh score.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with end-stage liver disease are known to demonstrate abnormal cardiovascular autonomic function, especially decreased HRV and BRS, and inappropriate circulatory response to various stimuli [11,12,28,29]. Moller et al [11] suggested that head-up tilt can induce abnormalities in sympathetic control and vascular reactivity, which lead to hemodynamic instability in patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (87%) of patients who undergo LT suffer from autonomic dysfunction. [ 22 ] Four years mortality is 30% in patients of ESLD with dysautonomia compared to 6% without dysautonomia. [ 23 ] The degree of dysautonomia usually improves after LT in up to 63% of patients within 6–7 months.…”
Section: Cardiomyopathymentioning
confidence: 99%